Assessment of primary care physicians' knowledge of chronic kidney disease in Poland - Jazienicka-Kiełb, Alicja; Babicki, Mateusz; Krajewska, Magdalena; Oko, Andrzej; Kłoda, Karolina; Mastalerz-Migas, Agnieszka (Frontiers in Public Health, 2022)
Chronic kidney disease (CKD) affects 10-15% of the adult population worldwide and is a major societal problem. A latent course of the disease and little alarming, gradually increasing symptoms usually do not cause concern in patients and diagnostic vigilance in physicians. CKD is most often diagnosed in its end-stage when treatment options are extremely limited. This study aims to assess the knowledge of CKD among primary care physicians (PCPs) in Poland. A CAWI survey was conducted based on an authors' own questionnaire that consisted of two parts. The first part concerned patients' socioeconomic data while the second part consisted of nine single- and multiple-choice questions assessing knowledge of the criterion for diagnosis, risk factors, diagnostic evaluation, and course of CKD. A total of 610 physicians took part in the survey, including 502 (82.3%) who fully completed the questionnaire. Women accounted for 83.1% of the study group. The mean age of the study group was 37.4 ± 10.1 years. Specialists or resident physicians in family medicine accounted for 79.9% of respondents and 93.8% of physicians are those who mainly work in primary care settings. In the knowledge test, the mean score obtained by physicians was 6.5 ± 1.3 out of possible 9, with only 2.4% of respondents answering all questions correctly. According to the survey, 78.4% of respondents correctly indicated the criterion for the diagnosis of CKD, while only 68.9% identified a test for increased urinary albumin loss as the one of the greatest diagnostic values in the early stages of CKD. More than half, 63.1%, of physicians selected the correct set of answers in the multiple-choice question regarding CKD risk factors. Despite a fairly high level of knowledge among family medicine physicians regarding the causes, risk factors and course of CKD, there is a need for further education and an increase in the factual information held by this professional group, especially that the vast majority of PCPs declare a desire to expand their knowledge and believe that this will help them in their daily clinical practice.